2011
DOI: 10.4187/respcare.01021
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Assist Ventilation and Neurally Adjusted Ventilatory Assist

Abstract: Patient-ventilator synchrony is a common problem with all patients actively triggering the mechanical ventilator. In many cases synchrony can be improved by vigilant adjustments by the managing clinician. However, in most institutions clinicians are not able to spend the time necessary to ensure synchrony in all patients. Proportional assist ventilation (PAV) and neurally adjusted ventilatory assist (NAVA) were both developed to improve patient-ventilator synchrony by proportionally unloading ventilatory effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 69 publications
(31 reference statements)
1
46
1
8
Order By: Relevance
“…The catheter is placed so the electrodes are at the level of the diaphragm. 32,33 When positioned properly, the EAdi signal can accurately and reliably trigger and cycle a positive-pressure breath, independent of air leak. Additionally, the magnitude of the inspiratory pressure assist is a product of the EAdi signal and the pre-set NAVA level.…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…The catheter is placed so the electrodes are at the level of the diaphragm. 32,33 When positioned properly, the EAdi signal can accurately and reliably trigger and cycle a positive-pressure breath, independent of air leak. Additionally, the magnitude of the inspiratory pressure assist is a product of the EAdi signal and the pre-set NAVA level.…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…60 NAVA has been reported to improve synchrony during NIV when a helmet is used. 25 For PAV, Gay et al 61 reported better patient tolerance with PAV, compared to PSV during NIV.…”
Section: Mode Asynchronymentioning
confidence: 99%
“…16 Neurally adjusted ventilatory assist (NAVA) operates similarly to PAV. 17 The only difference is that NAVA proportionally unloads the patient's inspiratory work of breathing by applying airway pressure per each microvolt increase in the diaphragmatic electromyographic signal. Overall, the application of ventilatory assistance is the same with PAV or NAVA: The greater the patient effort, the greater the ventilator pressure, and the lower the patient effort the lower the ventilator pressure.…”
Section: See the Original Study On Page 1527mentioning
confidence: 99%